Taming the beast : Wall Street's imperfect answers to making money - Light, Larry, 1959- (Wiley, 2011)
"A compelling financial narrative on flexible strategies investors can use to protect their assets Which is the best strategy for protecting your investments? Value investing? Indexing? Hedging? Growth investing? Asset allocation? It all depends upon the market because, although Wall Street has tried time and time again to devise a single system to tame the beast, the only thing that's constant about the market is that it's always changing and no one system will work perfectly to protect your assets each and every time. Taming the Beast: Wall Street's Imperfect Answers to Making Money presents the various strategies, and shows you how the best strategy is to be both flexible and nimble. Details the origins and evolutions of Wall Street's most popular trading strategies Describes who originated the strategy, and those who contributed to it Analyzes each strategy's strengths and weaknesses As Benjamin Graham noted in the 1930s, investors would be well advised to avoid getting mired in one set of beliefs. Times change, and so do markets. The key is to be flexible. Taming the Beast shows you how."--